EFFECTS OF NEW METROPOLITAN LAW NO.6360 TO RURAL DEVELOPMENT IN TURKEY - Halil Kızılaslan; Tayfur Ünal; Nuray Kızılaslan (Journal of New Theory)
– Actually implementing of Law No. 6360 by the year 2014 has brought many changes in urban and rural areas. The villages which lost their legal entity and turned into a neighborhood are considered to be affected more. At point of rural development, positive and negative effects of these changes on the local people are important. Local people living in rural are unable to grasp the impact of the law. Positively, in the future; since the villages will turn to the neighborhoods the social structures are likely to change and the level of consciousness will be increased. Negatively, agricultural production is expected to be stopped and financial difficulties will be seen. Besides, the term “rural” starts to disappear, thus traditional, folkloric and cultural heritage values will be lost. In order to eliminate the negative effects of this law, decision makers shall implement necessary plans and programs urgently. If no measures are taken, it will result in direct and indirect destruction in the future